Is Android or iPhone the platform for innovation in imaging informatics. - Shih G; Lakhani P; Nagy P (Journal of Digital Imaging, 2010)
It is clear that ubiquitous mobile computing platforms will be a disruptive technology in the delivery of healthcare in the near future. While radiologists are fairly sedentary, their customers, the referring physicians, and the patients are not. The need for closer collaboration and interaction with referring physicians is seen as a key to maintaining relationships and integrating tightly with the patient management team. While today, patients have to settle for their images on a CD, in short time, they will be taking them home on their cell phone. As PACS vendors are moving ever outward in the enterprise, they are already actively developing clients on mobile platforms. Two major contenders are the Apple's iPhone and the Android platform developed by Google. These two designs represent two entirely different architectures and business models.